Oligodendrocytes and CNS myelin are nonpermissive substrates for neurite growth and fibroblast spreading in vitro - Schwab, ME (J Neurosci, 1988)
To study the interaction of neurons with CNS glial cells, dissociated sympathetic or sensory ganglion cells or fetal retinal cells were plated onto cultures of dissociated optic nerve glial cells of young rats. Whereas astrocytes favored neuron adhesion and neurite outgrowth, oligodendrocytes differed markedly in their properties as neuronal substrates. Immature (O4+, A2B5+, GalC-) oligodendrocytes were frequently contacted by neurons and neurites. In contrast, differentiated oligodendrocytes (O4+, A2B5-, GalC+) represented a nonpermissive substrate for neuronal adhesion and neurite growth. When neuroblastoma cells or 3T3 fibroblasts were plated into optic nerve glial cultures, the same differences were observed; differentiated oligodendrocytes were nonpermissive for cell adhesion, neurite growth, or fibroblast spreading. These nonpermissive oligodendrocytes were characterized by a radial, highly branched process network, often contained myelin basic protein, and may, therefore, correspond to cells actively involved in the production of myelin-like membranes. Isolated myelin from adult rat spinal cord was adsorbed to polylysine-coated culture dishes and tested as a substrate for peripheral neurons, neuroblastoma cells, or 3T3 cells. Again, cell attachment, neurite outgrowth, and fibroblast spreading was strongly impaired. General physicochemical properties of myelin were not responsible for this effect, since myelin from rat sciatic nerves favored neuron adhesion and neurite growth as well as spreading of 3T3 cells. These results show that differentiated oligodendrocytes express nonpermissive substrate properties, which may be of importance in CNS development or regeneration.